2022
DOI: 10.1111/emre.12515
|View full text |Cite
|
Sign up to set email alerts
|

Organizational control in the context of remote working: A synthesis of empirical findings and a research agenda

Abstract: The increasing diffusion of remote working puts organizational control in the foreground. As employees work at a distance from traditional offices and/or are geographically dispersed, companies are called upon to influence their willingness to act in accordance with a company's vision, values, and objectives. To date, a comprehensive understanding of how organizational control is implied in remote work arrangements (RWAs) is still lacking. To fill this gap, a research synthesis—that is, a systematic review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 175 publications
(207 reference statements)
6
41
0
1
Order By: Relevance
“…The study found that manager and peer support enhance the self-efficacy of employees while WFH (and therefore H3 and H4 were supported). This concurs with the findings of earlier studies in this area, which suggested that organizational support can enhance both individual and organizational outcomes when WFH (Pianese et al, 2022). In WFH contexts, support from managers and peers has been found to generate self-efficacy among employees due to knowledge sharing and the possibility of clarifications (Kashive et al, 2021).…”
Section: Theoretical Implicationssupporting
confidence: 90%
“…The study found that manager and peer support enhance the self-efficacy of employees while WFH (and therefore H3 and H4 were supported). This concurs with the findings of earlier studies in this area, which suggested that organizational support can enhance both individual and organizational outcomes when WFH (Pianese et al, 2022). In WFH contexts, support from managers and peers has been found to generate self-efficacy among employees due to knowledge sharing and the possibility of clarifications (Kashive et al, 2021).…”
Section: Theoretical Implicationssupporting
confidence: 90%
“…For example, with a sudden change in work arrangements, managers should pay attention to the vulnerability of trust in the relationship with employees and find ways to reconfirm the established trust. The work from home schedule changes the methods a manager might use to manage employee performance, which may necessitate additional management training ( Pianese, Errichiello, & da Cunha, 2022 ). Employee feelings of felt mistrust may increase if managers change from quiet observation and casual face-to-face conversations to blunt explicit inquiries about performance or fail to provide support to accommodate disruptions of job duties, work conditions, and working schedules.…”
Section: Discussionmentioning
confidence: 99%
“…Our most important results are that adjustment to forced telework has been harder for some based on personality types. Presenting themselves as “reputable employees,” who do not need strict monitoring (Pianese et al, 2022, p. 10), is taxing for some types of employees. That is one possible mechanism identified in a recent research synthesis of telework before and during the pandemic, which might link personality types to work alienation (Pianese et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Presenting themselves as “reputable employees,” who do not need strict monitoring (Pianese et al, 2022, p. 10), is taxing for some types of employees. That is one possible mechanism identified in a recent research synthesis of telework before and during the pandemic, which might link personality types to work alienation (Pianese et al, 2022). Furthermore, through analyses of prepandemic and pandemic work alienation and work conditions among our sample, we have been able to identify the organizational management best practices that are most promising to reduce alienation in this context.…”
Section: Discussionmentioning
confidence: 99%